ANALYSIS OF LABOR ABSORPTION IN 154 DISTRICTS / CITIES ON THE ISLAND OF SUMATRA: A PANEL DATA APPROACH - Asrini; Neng Murialti; Hadi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
Labor absorption is an important factor in promoting economic growth and community welfare, especially in the island of Sumatra. This study aims to analyze the effect oflabor absorption in 154 districty/city on the island of Sumatra. In this study, secondary data was analyzed using panel data regression with fixed effect model approach for the period 2017-2023 using STATA 17 software. The results showed that the variables of districty/city minimum wage and foreign investment together had a positive and significant effect on employment. Meanwhile, the variable of domestic investment and labor productivity together have a negative and significant effect on employment